Alternative Start Codon Connects eIF5A to Mitochondria - Pereira, Karina Danielle [UNESP]; Tamborlin, Leticia; Meneguello, Leticia [UNESP]; Gomes De Proenca, Andre Ricardo; De Paula Andrade Almeida, Isadora Cristina; Lourenco, Rogerio Ferreira; Luchessi, Augusto Ducati [UNESP] (Wiley-Blackwell, 2016)
Eukaryotic translation initiation factor 5A (eIF5A), a protein containing the amino acid residue hypusine required for its activity, is involved in a number of physiological and pathological cellular processes. In humans, several EIF5A1 transcript variants encode the canonical eIF5A1 isoform B, whereas the hitherto uncharacterized variant A is expected to code for a hypothetical eIF5A1 isoform, referred to as isoform A, which has an additional N-terminal extension. Herein, we validate the existence of eIF5A1 isoform A and its production from transcript variant A. In fact, variant A was shown to encode both eIF5A1 isoforms A and B. Mutagenic assays revealed different efficiencies in the start codons present in variant A, contributing to the production of isoform B at higher levels than isoform A. Immunoblotting and mass spectrometric analyses showed that isoform A can undergo hypusination and acetylation at specific lysine residues, as observed for isoform B. Examination of the N-terminal extension suggested that it might confer mitochondrial targeting. Correspondingly, we found that isoform A, but not isoform B, co-purified with mitochondria when the proteins were overproduced. These findings suggest that eIF5A1 isoform A has a role in mitochondrial function. (C) 2016 Wiley Periodicals, Inc.